Evolution of hybrid service delivery models in the organisation of the future - Lopes Da Silva, Vasco (My University, 2016)
The purpose of this research is to develop a model that will aid organisations in evaluating their criteria to move to a hybrid service delivery model and to review existing criteria to gain an understanding of the efficiencies or inefficiencies driving the model. The problem statement addressed by this research was to evaluate the considerations and requirements for organisations introducing hybrid service delivery models. A model was developed to aid organisations identifying the drivers or facilitators to successfully move into a hybrid service delivery model. The model, through literature, attempts to establish the drivers and impediments to successfully move into a hybrid service delivery model. The research uses a semi-quantitative methodology using Fuzzy Cognitive Mapping (FCM) introduced by Euler in 1736 (Papageorgiou & Stylios, 2008). The first known use of FCM as used in this paper can be attributed to Axelrod, as a result of showing the causal relationships between variables (Papageorgiou & Stylios, 2008). The findings of the study show that organisations want greater control over their end-to-end processes, the responses indicate that organisations would want to work in partnership with the service provider through a collaborative culture, which they believe would lead to improved quality of operational data and improved performance management of the operations. It must be noted that the reduced cost structure of operations as a facilitator to organisations selecting hybrid service delivery models ranked fifth across the sixteen variables, indicating that organisations are changing their approach from a pure cost saving mind set to a more holistic mind set. The research implies that further studies can be done about the maturity of the models and the organisations themselves; this includes the ability of the organisation and its employees to embrace change.
MBA
Keywords: Organizational change -- South Africa. Strategic planning -- South Africa.